Cassava research program at Tamil Nadu Agricultural University (TNAU) in India - Thamburaj, S. (International Center for Tropical Agriculture, 1998)
Cassava is cultivated in Tamil Nadu in an area of 85,983 ha with an annual production of about 2.5 million t of roots (1993-94). At the world level, Tamil Nadu ranks first in yield, with 28.7 t/ha, as compared to the Indian average of 22.8 and a world average of 9.6 t/ha. In Tamil Nadu cassava is grown mainly in Salem and Kanyakumari districts located in the dry western zone (60% irrigated and 40% rainfall) and the high rainfall southern zone (mostly rainfed), respectively. The area under cassava is increasing in other districts of Tamil Nadu as well.